If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2) * 2 + (y + -12) * 2 = 36 Reorder the terms: (2 + x) * 2 + (y + -12) * 2 = 36 Reorder the terms for easier multiplication: 2(2 + x) + (y + -12) * 2 = 36 (2 * 2 + x * 2) + (y + -12) * 2 = 36 (4 + 2x) + (y + -12) * 2 = 36 Reorder the terms: 4 + 2x + (-12 + y) * 2 = 36 Reorder the terms for easier multiplication: 4 + 2x + 2(-12 + y) = 36 4 + 2x + (-12 * 2 + y * 2) = 36 4 + 2x + (-24 + 2y) = 36 Reorder the terms: 4 + -24 + 2x + 2y = 36 Combine like terms: 4 + -24 = -20 -20 + 2x + 2y = 36 Solving -20 + 2x + 2y = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 2x + 20 + 2y = 36 + 20 Reorder the terms: -20 + 20 + 2x + 2y = 36 + 20 Combine like terms: -20 + 20 = 0 0 + 2x + 2y = 36 + 20 2x + 2y = 36 + 20 Combine like terms: 36 + 20 = 56 2x + 2y = 56 Add '-2y' to each side of the equation. 2x + 2y + -2y = 56 + -2y Combine like terms: 2y + -2y = 0 2x + 0 = 56 + -2y 2x = 56 + -2y Divide each side by '2'. x = 28 + -1y Simplifying x = 28 + -1y
| 15x-10y=20 | | 2.5x^2-8*x=20 | | -6n+(-12)+4n= | | Log(x+2)+log(x-1)= | | 6+6r=12 | | 7/(x-8)=3/x | | 3x-8=-4x-92 | | 50x=80x | | 15=46-(2y+1) | | (4-1/3x)^3 | | 64-16y+2y^2=32 | | 4w+14=46 | | X^2+y^2+41=0 | | og(x+2)+log(x-1)=1 | | 3/5x1/5 | | 4x(3+8)-7= | | -7y-24=-8-9 | | 2x-(3-7x)+4(3-x)=7x-3(x-1) | | 4w-4x-y+3w+18x-8y= | | 2x+8=3-2x | | 1=9-3 | | T-(x-8)=-2 | | 18P-226=48 | | (x-4)(x^2+3)-(x-4)(6x-2)=0 | | -10+4x=2x-16 | | 70=10u | | 5x/95 | | 13+4(x+3)=105 | | 5+3A=7A-56 | | 3a+5=4 | | 2x^2+5x+(3-3k)=0 | | n^2-22n+40=0 |